The narrative structure in the poetry of Abdul-Amir Al-Hussary - Mahnoush, Hazem Dana; Abbas, Haider Fadel (Al-Adab Journal, 2020)
The phenomenon of spinning in the pre-Islamic era, the emergence of Islam, the Umayyad era, and the Abbasid era enjoyed many studies, and most of these studies that formed this prominent phenomenon in Arab poetry were concerned, as did the other section of those studies concerned with the artistic effect of spinning hair in terms of construction and installation, and rarely these studies were subject to monitoring The civilizational effect of this phenomenon, and if you were exposed to something of that, it is within the limits of the transient references that do not constitute an interdependent unit, and from here I found the topic (the narrative structure in the poetry of Abd al-Amir al-Husayiri) passion, love and passion in myself, as long as I was eager to study a topic related to researching the glorious heritage of our nation, as I am d Meh heritage related to the subject of great importance because of its active presence in the tightening weft cultural fabric and knowledge of the nation.